IMPORTANCE OF CHEMICAL FERTILIZERS IN PEA PRODUCTION IN IRRIGATED FIELDS - Otakulova Dilfuza Azamatovna (European Journal of Agricultural and Rural Education, 2024)
In the arid regions of the Kashkadarya region, the main task is to select suitable crops that are resistant to abiotic factors and capable of physiological adaptation. In this article, an important factor in the formation of pea yields is the use of a mixture of mineral fertilizers and growth-stimulating microplants in the light gray soil conditions of the Kashkadarya region to obtain high yields from pea varieties. The photosynthetic activity of plants was assessed. Currently, in various large research centers around the world, much attention is paid to the creation of pea varieties that are resistant to extreme conditions, the study of the morpho-physiological characteristics of the created varieties, increasing their nutritional value, determining the dependence of yield, the quality of crops, cultivation methods, and improving technology elements cultivation.